2019
DOI: 10.1101/19008672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of Nab-paclitaxel in breast cancer: a meta-analysis

Abstract: Worldwide breast cancer is the leading cause of cancer related death in women. Paclitaxel is an effective drug used for the treatment of breast cancer but it has many side effects. Nab-paclitaxel (nanoparticle albumin-bound paclitaxel) is an FDA approved drug for the treatment of breast cancer. Currently many clinical trials are conducted to deliver nab-paclitaxel into the tumor cells. But the efficacy and safety of this nab-paclitaxel over conventional paclitaxel still remains questionable. So, we performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Indeed, some clinical trials and meta-analyses showed the superiority of nab-paclitaxel to solvent-based paclitaxel, in terms of efficacy and safety, in patients with metastatic breast cancer and patients with pancreatic cancer [12][13][14]. However, other studies have been done and show that there is no difference between paclitaxel and nab-paclitaxel in their efficacy and safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some clinical trials and meta-analyses showed the superiority of nab-paclitaxel to solvent-based paclitaxel, in terms of efficacy and safety, in patients with metastatic breast cancer and patients with pancreatic cancer [12][13][14]. However, other studies have been done and show that there is no difference between paclitaxel and nab-paclitaxel in their efficacy and safety profile.…”
Section: Introductionmentioning
confidence: 99%